2013
DOI: 10.1080/17482798.2012.739780
|View full text |Cite
|
Sign up to set email alerts
|

Online Risks

Abstract: Exposure to online risks does not necessarily result in harm, but some groups of children prove to be less resilient than others when facing a potentially harmful situation online. The aim of this article is to better understand and explain which children under which social conditions are more likely to be more or less resilient. Children with low self-efficacy and more psychological difficulties are more vulnerable online as they experience stronger negative feelings and are more likely to go offline for a wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 37 publications
0
23
1
Order By: Relevance
“…To date, resilience has been rather overlooked in the studies on cybervictimization despite its potential role for promoting positive outcomes even in the presence of harmful online experiences. In cyberspace, resilience has been conceptualized as "being able to deal with a negative experience online, i.e., not remaining passive but displaying problem-solving coping strategies in order to protect oneself from future harm" [19] (p. 60). The few existent studies [11,12,20] on the role of resilience in moderating the impact of cybervictimization are promising.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, resilience has been rather overlooked in the studies on cybervictimization despite its potential role for promoting positive outcomes even in the presence of harmful online experiences. In cyberspace, resilience has been conceptualized as "being able to deal with a negative experience online, i.e., not remaining passive but displaying problem-solving coping strategies in order to protect oneself from future harm" [19] (p. 60). The few existent studies [11,12,20] on the role of resilience in moderating the impact of cybervictimization are promising.…”
Section: Introductionmentioning
confidence: 99%
“…These include risk factors-since resilience, by nature, is activated only in conjunction with life-threatening events-and protective factors, where "protection may derive from what people do to deal with stress or adversity" [21] (p. 8). According to Rutter's suggestion, coping strategies can be thus conceptualized as pathways to resilience [13] (p. 123), as they represent the "efforts to adapt to stress or other disturbances by a stressor or adversity in order to protect oneself from the psychological harm of risky experiences" [19] (p. 61).…”
Section: Introductionmentioning
confidence: 99%
“…Organizations that are strong in cyberresilience will be loyal to serve its purpose (whether service or product), tough in terms of facing crisis and challenges, and is systematically able to recover from setbacks and disadvantageous situations that threaten its integrity, availability, and confidentiality from outside or within. This definition is often ameliorated to the extent that it is applicable to the individual level, which translates to the concept of "online resilience" that serves as the opposition towards "online vulnerability" (Vandoninck, d'Haenens, & Roe, 2013). People with high level of cyber-resilience do not easily feel negative emotions or revert back to the offline world, such as in a situation where they are challenged or demotivated in using an IoT device.…”
Section: Cyber-resiliencementioning
confidence: 99%
“…People with high level of cyber-resilience do not easily feel negative emotions or revert back to the offline world, such as in a situation where they are challenged or demotivated in using an IoT device. Vandoninck et al (2013) in their research studying online sexual temptation among children and young teenagers found that there are a few determinant factors of online resilience, namely age, self-efficacy, pro-active coping response, digital literacy, and previous experiences in facing cyber-risks. What is interesting about this finding is that socio-economic status and parental mediation and monitoring do not correlate with cyber-resilience.…”
Section: Cyber-resiliencementioning
confidence: 99%
“…[54] We can even say that the security issues of online theft [55][56] and the jeopardy and susceptibility to hacking and phishing apply in full to online procedures of lending and borrowing money as alternative financing methods. [57] CONCLUSION AND INSIGHTS The paper aims to consider and analyze the overall state of alternative financing with a more detailed look at two prevailing forms: peer to peer lending, and crowdfunding, as compared to traditional financing method which is primarily the process of receiving a bank loan. This paper goes on to consider not just the benefits of the alternative financing but also the innovation, efficiency, effectiveness, and also risks involved.…”
Section: Efficiency and Innovations In Alternative Financingmentioning
confidence: 99%